The Effect of the Global Financial Crisis on Corporate Investment in Korea: From the Perspective of Costly External Finance - Dae hee Jeong (KDI Journal of Economic Policy, 2015)
This paper examines the effect of the global financial crisis on corporate investment in Korea. Specifically, the crisis was considered to have possibly constrained firm-level investment as the negative shock to the credit supply dramatically unfolded. As Duchin et al. (2010) demonstrated, if a negative supply-side shock is evident during a crisis period, larger cash holdings before the crisis will lead to fewer constraints to corporate investment, or vice versa. In order to investigate the supply-side effect of the crisis, we use firm-level financial data, including firms listed on the Korean stock market as well as small and medium-sized enterprises. We find that corporate investment declined significantly after the crisis, even if we control for factors associated with the demand side, such as contemporaneous capital productivity and cash flow. More importantly, the decline is positively and significantly related to cash holdings before the crisis, implying the negative effect of a credit supply shock. Small and medium enterprises experienced relatively sharp investment declines compared to those of larger firms, and the relationship between pre-crisis cash amounts and the degree of investment decline is greater than that in large firms. Additionally, we examine whether the negative effect persists up to the present, finding evidence that the cash-investment relationship continues in small and medium-sized enterprises.
Keywords: G01; G31; G32; 330; Financial crisis; corporate investment; credit supply; financial constraint; cash holdings